Dynamics of community-acquired meningitis syndrome outbreaks in southern France - Morsli, Madjid; Salipante, Florian; Kerharo, Quentin; Boudet, Agathe; Stephan, Robin; Dunyach-Remy, Catherine; Zandotti, Christine; Lavigne, Jean-Philippe; Drancourt, Michel (Frontiers in Microbiology, 2023)
In southern France, community-acquired meningitis syndrome (CAM) cases are typically clustered as outbreaks whose determinants remain unknown. This 61-month retrospective investigation in Nîmes and Marseille university hospital laboratories, yielded 2,209/20,779 (10.6%) documented CAM cases caused by 62 different microorganismes, represented by seasonal viral etiologies (78.8%), including enterovirus, Herpes Simplex Virus (HSV) and Varicella-Zoster Virus (VZV) (1,620/2,209=73.4%). Multi Correspondence Analysis revealed an association of infection with age and sex, with the risk of infection relatively higher in young men, as confirmed by Fisher’s exact test (p<103). Bacterial meningitis accounted for 20% of cases, mostly caused by Streptococcus pneumoniae in 27.4% of cases, Neisseria meningitidis in 12.5% and Haemophilus influenzae in 9.5% with bacteria/virus coinfection in 0.9%, and only six cases of documented fungal meningitis. In total, 62.6% of cases of which 88.7% were undocumented, arose from 10 outbreaks; with 33.2% of undocumented cases were aged > 60 years vs. 19.2% of documented cases (P <0.001), and viral infection was more common in the summer (87.5% in summer vs. 72.3% in other seasons, P <0.001). Outbreaks most often started in Nîmes and moved eastward toward Marseille at a 9 km/day speed, and these dynamics significantly correlated with the atmospheric temperature, especially during summer outbreaks; particularly, incidence of enterovirus-driven outbreaks correlated with temperature with correlation coefficients of 0.64 in Nîmes and 0.72 in Marseille, and its occurrence in Marseille lagged that in Nîmes by 1-2 weeks. Tracing CAM outbreak dynamics during this retrospective investigation in southern France yielded a speed of displacement that correlated with the variation in temperature between both cities, and these results provide clues for the next occurrence of undocumented outbreaks.